1978
DOI: 10.1152/jn.1978.41.4.1014
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic transmission without action potentials: input-output properties of a nonspiking presynaptic neuron

Abstract: 1. Input-output properties of the inhibitory synaptic connection between non-spiking neurons (EX1) and gastric mill (GM) neurons were examined in the stomatogastric ganglion of the spiny lobster, Panulirus interruptus. Current was injected into and the voltage was recorded during current injection, two independent microelectrodes were used. 2. The EX1-GM synaptic connection is a conductance-increase inhibitory type, with an input-output curve that resembles the curve for the squid giant synapse. There is a thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 0 publications
3
67
0
Order By: Relevance
“…Almost all of the previously published work studying graded synaptic transmission in the stomatogastric nervous system used single, long, square presynaptic current pulses (Maynard and Walton, 1975;Graubard, 1978;Graubard et al, 1980Graubard et al, , 1983Johnson and Harris-Warrick, 1990;Johnson et al, 1991Johnson et al, , 1995. Our study reveals that the amplitude of the postsynaptic response depends on the specific shape of the presynaptic waveform.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Almost all of the previously published work studying graded synaptic transmission in the stomatogastric nervous system used single, long, square presynaptic current pulses (Maynard and Walton, 1975;Graubard, 1978;Graubard et al, 1980Graubard et al, , 1983Johnson and Harris-Warrick, 1990;Johnson et al, 1991Johnson et al, , 1995. Our study reveals that the amplitude of the postsynaptic response depends on the specific shape of the presynaptic waveform.…”
Section: Discussionmentioning
confidence: 72%
“…The threshold for transmitter release is close to the resting potential, and synaptic release is both spike-mediated and graded (Maynard and Walton, 1975;Graubard, 1978;Graubard et al, 1980Graubard et al, , 1983Johnson and Harris-Warrick, 1990;Johnson et al, 1995). At some synapses the graded component of transmitter release is significantly larger than that evoked by action potentials and is the major contributor to network dynamics (Raper, 1979;Graubard et al, 1983;Hartline et al, 1988).…”
Section: Abstract: Graded Synaptic Transmission; Pyloric Network; Cementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown the usefulness of single, long, square pulses in the study of graded synaptic transmission in the STNS (Maynard and Selverston, 1975;Graubard, 1978;Johnson and HarrisWarrick, 1990;Manor et al, 1997). Figure 2 A shows simultaneous responses of the LP (middle trace) and PY (bottom trace) neurons to a 2 s presynaptic square pulse in both PD neurons from Ϫ60 to Ϫ20 mV (top trace) in TTX saline.…”
Section: Comparison Of the Dynamics Of The Ipsps From The Pacemaker Umentioning
confidence: 90%
“…The inhibitory synapses between the pacemaker ensemble and the LP and PY neurons use voltage-dependent (graded) release of neurotransmitter as the major form of transmission (Maynard and Walton, 1975;Graubard, 1978;Graubard et al, 1980;Johnson and Harris-Warrick, 1990;Johnson et al, 1995). To isolate this form of synaptic release, spikemediated transmission was blocked by superfusing the preparation with Panulirus saline containing 10 Ϫ7 M TTX (Biotium, Hayward, CA).…”
Section: Methodsmentioning
confidence: 99%